Experimental analysis of the feasibility of low-cost piezoelectric diaphragms in impedance-based SHM applications - Silva De Freitas, Everaldo [UNESP]; Guimarães Baptista, Fabricio [UNESP] (Elsevier, 2016)
Structural health monitoring (SHM) systems with damage detection based on the electromechanical impedance (EMI) method have received attention in recent decades because of the simplicity of the methodology, which is based on the use of small and lightweight piezoelectric transducers that operate simultaneously as sensors and actuators. Typically, the piezoelectric transducers used in the EMI method have been thin PZT (lead zirconate titanate) ceramics, which can be cut into different sizes and shapes. In this study, an experimental analysis of the feasibility of low-cost piezoelectric diaphragms, commonly known as buzzers, for damage detection based on the EMI method is presented. Diaphragms of different sizes were evaluated in aluminum beams, and the experimental results were compared with those obtained from a conventional PZT ceramic. Four types of experiments were performed: sensitivity estimation using the pencil lead break (PLB) method, analysis of the ability to detect structural damage using conventional impedance signatures and damage indices, analysis of temperature effects, and determination of the long-term reproducibility of the results. The results indicate that a conventional PZT ceramic and a diaphragm of similar size have similar reproducibilities and sensitivities to damage and temperature effects.
Keywords: Damage detection; Feasibility; Impedance; Piezoelectric diaphragms; PZT; SHM